ORGANIZATION OF SELF-INSTRUCTION WORK FOR STUDENTS OF TECHNICAL UNIVERSITY IN THE SYSTEM OF BASIC SCIENCE STUDIES - Vitaliy V. Larionov; Andrey M. Lider (Высшее образование в России)
Tomsk polytechnic university experience in organization of selfBinstruction work for bachelor and master degree students is discussed in the paper. SelfBinstruction work are organized on projectBbased cooperative learning methodology in studying physics - developing innovative ideas for implementation. The model of cooperative learning based on transformation of a standard problem to a project is developed and discussed. The model implementationis realized through specially designed virtual learning environment to provide development of competences prognosed to be in demand. Project work includes elements of development by students of their own product as a result of a learning process. Study guides and teaching aids have been developed; they contain system of tasks and assignments, which serve as a basis for approximating students learning activities to practical performance. As a result, students master methodology and means of performance realization, which can be implemented in research and development, design works.